Clinical characteristics and outcomes in COVID-19 in kidney transplant recipients: a propensity score matched cohort study - Delfino-Pereira, Polianna; Ventura, Vanessa das Graças José; Pires, Magda Carvalho; Ponce, Daniela; Carmo, Gabriel Assis Lopes do; Carmo, Lilian Pires de Freitas do; Paiva, Bruno Barbosa Miranda de; Schwarzbold, Alexandre Vargas; Gomes, Angélica Gomides dos Reis; Castro, Bruno Mateus de; Polanczyk, Carísi Anne; Cimini, Christiane Corrêa Rodrigues; et al. (Frontiers in Medicine, 2024)
Our study aimed to compare the clinical characteristics and outcomes of COVID-19 patients who received kidney transplants (KT) with those on chronic dialysis and patients without chronic kidney disease (CKD). This multicentric retrospective cohort included adult COVID-19 laboratory-confirmed patients admitted from March/2020 to July/2022, from 43 Brazilian hospitals. The primary outcome was in-hospital mortality. Propensity score analysis matched KT recipients with controls - patients on chronic dialysis and those without CKD (within 0.25 standard deviations of the logit of the propensity score) - according to age, sex, number of comorbidities, and admission year. This study included 555 patients: 163 KT, 146 on chronic dialysis, and 249 non-CKD patients (median age 57 years, 55.2% women). With regards to clinical outcomes, chronic dialysis patients had a higher prevalence of acute heart failure, compared to KT recipients, furthermore, both groups presented high in-hospital mortality, 34.0% and 28.1%, for KT and chronic dialysis patients, respectively. When comparing KT and non-CKD patients, the first group had a higher incidence of in-hospital dialysis (26.4% vs. 8.8%, p<0.001), septic shock (24.1% vs. 12.0%, p= 0.002), and mortality (32.5% vs. 23.3%, p= 0.039), in addition to longer time spent in the intensive care unit (ICU). In this study, chronic dialysis patients presented a higher prevalence of acute heart failure, compared to KT recipients, whereas KT patients had a higher frequency of complications than those without CKD, including septic shock, dialysis during hospitalization, and in-hospital mortality as well as longer time spent in the ICU.